Crisis Without Borders: What Does International Law Say About Border Closure in the Context of Covid-19? - Chetail, Vincent (Frontiers in Political Science, 2020)
This paper is assessing the legality of border closures decided by a vast number of countries with the view of limiting the spread of Covid-19. Although this issue has raised diverging interpretations in relation to International Health Regulations and regional free movement agreements, international human rights law provides a clear-cut answer: the rule of law stops neither at the border nor in times of emergency. Against this normative framework, border control can and must be carried out with the twofold purpose of protecting public health and individual rights, whereas border closure is unable to do so because it is by essence a collective and automatic denial of admission without any other form of process. This paper argues that blanket entry bans on the ground of public health are illegal under international human rights law. They cannot be reconciled with the most basic rights of migrants and refugees, including the principle of non-refoulement and access to asylum procedures, the prohibition of collective expulsion, the best interests of the child and the principle of nondiscrimination. The paper concludes on the ways to better integrate at the borders public health and human rights imperatives in due respect with the rule of law. In both law and practice, public health and migrant’s rights are not mutually exclusive. They can reinforce each other within a comprehensive human rights based approach to health and migration policies.